The effect of the Employ of Polomer Trainings on some Physical Capabilities, and The Performance Level of Some Basic Skills of Teen – Agers of Football, who are aged Between 13 years Up To 15 years (Journal of Human Sciences, 2020)
The importance of this study is that, The Employ op polomer  Trainings IS Consider  is one  of Types of The Musles Power Trainings, it used Some Types of Trainings That Lead to Some Degree of Flex ability and will decide The  Performance level of Some Basic skills of Teen – Acers of Football Plapers  The Study also Aimed to specify the effect of using polymer Trainings on some general physical capabilities. THE Sample of Research  is consisted of (20) Player of teen. Ages  aged: 13-15 Years from "Altalia"  football , club in Chat City The results of study indicated that clear improve Took place in scaling variable during USA of this program of Training, that prove considerable positive development in physical capabilities and the level of skills in football scope.